Toward Inclusive Plurilingualism: Adopting an Ethnography of Language Policy Approach at a Public University in Colombia - Quinn, Padraic Michael (Colombian Applied Linguistics Journal, 2025)
This paper describes an ethnographic approach to developing a formal language policy incorporating English as a Foreign Language (EFL) teaching in a Colombian public higher education institution. This study aimed to document the process undertaken for developing an institutional language policy that goes beyond solely teaching English and focuses more broadly on the recognition and promotion of plurilingualism and inclusion. Data was gathered from an ethnography of language policy approach including participant observations, qualitative analysis of existing institutional language documentation, surveys, and focus groups. Results suggest that adopting an ethnographical approach to language policy development provides a more inclusive way of considering the plurilingual realities of the region and not just the necessities of EFL teaching. By focusing on a single institution’s challenges, the paper sheds light on some considerations that other institutions can learn from, especially when recognizing the complex sociolinguistic context that is public higher education in Colombia.